Adenosine Metabolism Pathway Alterations in Frontal Cortical Neurons in Schizophrenia - Smita Sahay; Emily A. Devine; Christina F.-A. Vargas; Robert E. McCullumsmith; Sinead M. O’Donovan (Cells)
Schizophrenia is a neuropsychiatric illness characterized by altered neurotransmission, in which adenosine, a modulator of glutamate and dopamine, plays a critical role that is relatively unexplored in the human brain. In the present study, postmortem human brain tissue from the anterior cingulate cortex (ACC) of individuals with schizophrenia (n = 20) and sex- and age-matched control subjects without psychiatric illness (n = 20) was obtained from the Bronx–Mount Sinai NIH Brain and Tissue Repository. Enriched populations of ACC pyramidal neurons were isolated using laser microdissection (LMD). The mRNA expression levels of six key adenosine pathway components—adenosine kinase (ADK), equilibrative nucleoside transporters 1 and 2 (ENT1 and ENT2), ectonucleoside triphosphate diphosphohydrolases 1 and 3 (ENTPD1 and ENTPD3), and ecto-5′-nucleotidase (NT5E)—were quantified using real-time PCR (qPCR) in neurons from these individuals. No significant mRNA expression differences were observed between the schizophrenia and control groups (p > 0.05). However, a significant sex difference was found in ADK mRNA expression, with higher levels in male compared with female subjects (Mann–Whitney U = 86; p < 0.05), a finding significantly driven by disease (t(17) = 3.289; p < 0.05). Correlation analyses also demonstrated significant associations (n = 12) between the expression of several adenosine pathway components (p < 0.05). In our dementia severity analysis, ENTPD1 mRNA expression was significantly higher in males in the “mild” clinical dementia rating (CDR) bin compared with males in the “none” CDR bin (F(2, 13) = 5.212; p < 0.05). Lastly, antipsychotic analysis revealed no significant impact on the expression of adenosine pathway components between medicated and non-medicated schizophrenia subjects (p > 0.05). The observed sex-specific variations and inter-component correlations highlight the value of investigating sex differences in disease and contribute to the molecular basis of schizophrenia’s pathology.